Implementasi Pembelajaran Kontekstual Berbasis Budaya Lokal Penginyongan - Harisatunisa, Harisatunisa; Sauqi, Chubby (Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
The concept of contextual learning seeks to give meaning to each learning activity by trying to connect new knowledge with previous knowledge possessed by students. Contextual learning is also a means of building awareness and shaping the self-identity of students as part of a society that has a culture. Learning activities must help humans in carrying out their existence in the environment where they live, both in the smallest scope to the national scope as citizens. This study tries to describe the Implementation of Local Culture-Based Contextual Learning in Banyumas and the obstacle of implementation . This research uses qualitative field research with case studies. This study found that the implementation of contextual learning based on local culture was carried out by using (1) physical culture such as food, Banyumas musical instruments as a source of learning (2) field trips and observations as learning strategies of Contextual Learning method. The obstacles of contextual learning practice in this school are (1) the number of teacher who understand about this culture (2) most of parents have different cultures.